2001
DOI: 10.1093/ejo/23.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Congenital tooth anomalies and malocclusions: a genetic link?

Abstract: The aim of the present study was to investigate putative relationships between different malocclusions such as Class III and Class II division 1, and congenital tooth anomalies. Two-hundred Class III and 215 Class II division 1 patients were examined for the presence of any of the following congenital tooth anomalies: maxillary incisor hypodontia, maxillary canine impaction, transpositions, supernumerary teeth, and tooth agenesis. Their occurrence rates were then calculated as a percentage of the total sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
59
3
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(88 citation statements)
references
References 10 publications
13
59
3
13
Order By: Relevance
“…In addition, dental anomalies have been associated with Class II, division 2 malocclusion (9), thus indicating a strong genetic influence in the development of this type of malocclusion (10). On the other hand, Class III and Class II, division 1 malocclusions have a pattern of occurrence of anomalies similar to that found in the general population (11).…”
Section: Introductionsupporting
confidence: 77%
See 3 more Smart Citations
“…In addition, dental anomalies have been associated with Class II, division 2 malocclusion (9), thus indicating a strong genetic influence in the development of this type of malocclusion (10). On the other hand, Class III and Class II, division 1 malocclusions have a pattern of occurrence of anomalies similar to that found in the general population (11).…”
Section: Introductionsupporting
confidence: 77%
“…On the other hand, Basdra et al (11) found no statistically significant differences between the anomalies and the type of malocclusion. These authors evaluated only 83 patients presenting anomalies with Class III or Class II division 1 malocclusions, a number well below the 562 patients evaluated in the current study.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…1,2,11,14,22,[25][26][27] The molar class distributions for PDCG subjects mostly showed Angle Class I (50%) for both the impacted and the nonimpacted sides. BDCG patients were characterized by a prevalence of Angle Class II in the impacted side (61.3%) compared to a higher prevalence of Angle Class I in the nonimpacted side (54.8%).…”
Section: Discussionmentioning
confidence: 99%